Maternal satisfaction with intrapartum care and associated factors among mothers who gave birth in public hospitals of the South West Shewa Zone, Ethiopia, 2022 - Fikadu Tolesa; Adugna Alemu; Moges Beya; Mulugeta Feyisa; Andualem Gezahagn; Abdi Negash; Erean Shigign; Asfaw Getaye; Abraham Negash; Bacha Merga (Frontiers Media S.A., 2023)
BackgroundMaternal satisfaction with intrapartum care is a multidimensional assumption of satisfaction with self and with the physical environment of the delivery ward and quality of care. Maternal satisfaction with intrapartum care affects the selection of birthplace and helps to identify gaps between actual and intended healthcare outcomes. This study aims to assess factors that affect maternal satisfaction with intrapartum care.ObjectivesTo assess maternal satisfaction with intrapartum care and associated factors among mothers who gave birth in public hospitals in the South-west Shewa Zone, Ethiopia, 2022.MethodsA cross-sectional study approach among 420 mothers was conducted between April 14 and June 14, 2022. Systematic random sampling was used to select mothers for face-to-face interviews every two intervals. Bivariate and multivariable logistic regression analyses were carried out. P-values of <0.25 in association with study variables were transferred to multivariable logistic regression models. An adjusted odds ratio with a 95% confidence interval was computed, and p-values of <0.05 were considered statistically significant in the multivariable model. The results of this study are presented using text, tables, and charts.ResultsData were collected from 420 participants, and 413 mothers completed the interview, giving a response rate of 98.33%. The overall maternal satisfaction with intrapartum care was 245 (59.32%) [95% CI: 55-64]. Mothers who were considered normal during labor and delivery (AOR = 2.57 (95% CI: 1.30-5.07), had a labor duration of 12 h or less (AOR = 1.59 (95% CI: 1.03-2.44), and experienced a waiting time of <15 min (AOR = 2.06 (95% CI: 1.21-3.52) were significantly associated with maternal satisfaction with intrapartum care.Conclusion and RecommendationsMore than half of mothers were satisfied with the overall intrapartum care they received. Health facility managers and healthcare providers work together to improve maternal satisfaction with intrapartum care.